La temporalidad como estructura de L’Action (1893) de Maurice Blondel - Perkins, Patricio (ARFIL y UNL, 2018)
This paper aims to offer an analysis of the estructure of Maurice Blondel’s L’Action (1893) in three different levels taking into account as a model the triadic configuration of temporality. The first level is implicit in the analysis of action made in the Introduction to the work; the second level consists in the analysis of passivity described in the first moment of the fourth part; the third level contains the whole work in its global sense, extending itself to the phenomenon of action, the argument about the only necessary being and the alternative of action. I pretend to prove that the past, present and for-coming dimensions of temporality are at the base of the comprehension of this work.